Potential Use of Broadband Acoustic Methods for Micronekton Classification - Verma, A.; Kloser, Rudy; Duncan, Alec (Australian Acoustical Society, 2017)
Broadband acoustic methods are an emerging technology with potential use in identification and classification of marine organisms. The application of broadband methods to scientific surveys of mesopelagic micronektons (animals of 2–20 cm length found at depths of 200–1000 m) is described. The principles of the broadband system are briefly outlined with particular emphasis on its use for micronekton detection and identification employing the TS-frequency curve of single targets. The use of acoustic scattering models to determine characteristics of the marine organism such as size and material properties is also discussed. As an example of the application of this technique, broadband echosounders mounted on a depth-profiling platform were used to collect high-frequency (55–160 kHz) acoustic data from mesopelagic depths (up to 600–1000 m) of the Great Australian Bight region. Some example results from narrowband and broadband echosounders are compared. The resulting frequency-dependent target strength curves of selected targets enabled classification into different acoustic groups, demonstrating the significant advantage provided by the broadband system. There is still a large gap between the achievable acoustic classification and the ultimate aim of species level classification, and to this end some limitations of broadband echosounder systems in identifying targets are discussed along with the use of video and still cameras to assist in the interpretation of acoustic data.